Diversity of oxytocin neurons: beyond magno- and parvocellular cell types? - Althammer, Ferdinand; Grinevich, Valéry (Journal of neuroendocrinology, 2018)
The hypothalamic neuropeptide oxytocin (OT), which is evolutionarily conserved among different species throughout the animal kingdom, is a key modulator of a variety of socio-emotional behaviors such as fear, trust and empathy. OT cells in the mammalian hypothalamus have been traditionally divided into two distinct types - magnocellular (magnOT) and parvocellular (parvOT) or preautonomic neurons. This distinction is based on OT cell sizes and shapes, projections, electrophysiological activity and functions. Indeed, while neuroendocrine magnOT neurons are known to primarily project their axons to the posterior pituitary and to a number of forebrain regions, non-neuroendocrine parvOT neurons have been seen as the main source of OT innervation of the brainstem and spinal cord to control autonomic functions and pain perception. However, very recent findings demonstrated distinct genetic profiles in OT neurons, allowing discrimination of at least four types of cells expressing OT. Furthermore, unexpected axonal projections of parvOT neurons to the forebrain and magnOT neurons to the midbrain have been newly reported. In this review, we focus on the detailed analysis of methods of distinction between OT cell types, in- and output sites, morphology as well as on the direct connectivity between OT neurons and its physiological significance. At the end, we propose a hypothesis that the central OT system is composed of more than just two OT cell types, which should be further verified by the application of available genetic and anatomical techniques.
Online veröffentlicht am 12. Oktober 2017
Gesehen am 13.12.2023